The Practice Of "Attesang" In Developing The Economy Of Farmers And Capital Owners Based On Al-Adl In Gowa Regency (International Journal of Environmental Sciences, 2025)
The objectives to be achieved in this study are: 1) To analyze the implementation of the cooperative relationship pattern in the Attesang Practice in Building the Economy of Farmers and Capital Owners Based on Al-Adl in Gowa Regency. 2) To analyze the suitability of the profit sharing of the Attesang practice in the Al-adl perspective in Gowa Regency. 3) To reveal how the application of the Attesang Practice in the Al-Adl perspective improves the economy of farmers and capital owners in Gowa Regency. The research method used was descriptive research analyzed qualitatively. Data sources were obtained from farmers, capital owners, traditional and religious leaders, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that: 1) the implementation of the "Attesang" Practice in the cooperative relationship between farmers and capital owners in Gowa Regency is not fully fulfilled, where farmers have not been able to position themselves as working partners. The "Attesang" Practice in the perspective of Al-Adl is not appropriate because the rights of farmers in marketing their agricultural products are dominated by capital owners, transparency of decision making is not in accordance with Al-Adl; 2) The "Attesang" Practice in Gowa Regency uses Muzara'ah and Mukhabarah contracts which are in accordance with the profit sharing agreement in Islam; 3) With the existence of the "Attesang" Practice based on Al-Adl, it is able to build in increasing the income of farmers and capital owners, able to recruit workers in the agricultural sector and able to reduce unemployment, economic improvement of farmers and capital owners comes from different portions, where farmers get income according to the area of land they cultivate while capital owners get income according to the number of partners or farmers they accompany in cooperation, so that the economic improvement of both is different. Implications of the research: 1) Most farmers do not understand themselves as working partners; 2) in practice, it is found that farmers use their rights very little in seeking markets; 3) in making decisions, they are dominated by capital owners; 4) the capacity of farmers and capital owners is different, while profit sharing is a model of cooperation not as workers, the status of farmers cannot yet position themselves as working partners; and 5) the economic improvement of farmers is different between farmers and capital owners, where farmers get results depending on the area of land they manage, while capital owners depend on the number of farmers they cooperate with..